Method of physical simulation of macro processes of solidification of castings on transparent models and liquids. - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2021)
The technique of physical modeling of macro processes of solidification of castings on transparent models and liquids has been developed. The model liquids may be water with different salt contents. Glass bottles can be used for transparent models. Thermal insulation of the top of the model is required. The developed technique allows to investigate the effect of dissolved gases on the microstructure of castings. It has been shown that gases dissolved in liquids have a direct effect on the solidification process and its kinetics. It has been shown that hot water containing less dissolved air than cold water solidifies in the freezer faster than cold water.